2014
DOI: 10.1097/wnp.0000000000000019
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Double Banana

Abstract: The findings advocate for the use of these digital EEG technology-derived analysis methods in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 29 publications
(24 reference statements)
0
20
0
Order By: Relevance
“…Peak negativity was defined as phase reversal in longitudinal and transversal bipolar montages, and maximum negative amplitude of the signals in common average montage. In addition, scalp-topography of the voltage distribution were visualized using voltage-maps (Rosenzweig et al 2014). In case of disagreement in scoring, this was resolved in joint reading sessions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peak negativity was defined as phase reversal in longitudinal and transversal bipolar montages, and maximum negative amplitude of the signals in common average montage. In addition, scalp-topography of the voltage distribution were visualized using voltage-maps (Rosenzweig et al 2014). In case of disagreement in scoring, this was resolved in joint reading sessions.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study demonstrated that adding six electrodes in the inferior temporal chain to the 10-20 array, in the long-term video-EEG monitoring, significantly increased the accuracy of estimating the source of the ictal signals in patients with foci in the temporal lobe, as evaluated by a panel of trained experts (Rosenzweig et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Five different source analysis methods were applied: phase-mapping (PM), dipole fitting, CLARA, cortical-CLARA and minimum norm estimation (MN). The analysis methods are described in detail elsewhere [12], [13]. Briefly:…”
Section: Methodsmentioning
confidence: 99%
“…By combining the real and imaginary peak FFT coefficients at different phase angles, phase maps were calculated, i.e., voltage maps at various relative latencies by transforming phase into time [13], [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation